2021
DOI: 10.1101/2021.05.12.443888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA vaccine-induced T cells respond identically to SARS-CoV-2 variants of concern but differ in longevity and homing properties depending on prior infection status

Abstract: While mRNA vaccines are proving highly efficacious against SARS-CoV-2, it is important to determine how booster doses and prior infection influence the immune defense they elicit, and whether they protect against variants. Focusing on the T cell response, we conducted a longitudinal study of infection-naive and COVID-19 convalescent donors before vaccination and after their first and second vaccine doses, using a high-parameter CyTOF analysis to phenotype their SARS-CoV-2-specific T cells. Vaccine-elicited spi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Notably, CD4 + T-cell frequency was higher compared to that observed for the CD8 + T cells. These data agree with the results from the HCWs cohorts (5,(27)(28)(29)(30)(31) and the COVID-19 convalescent subjects (17,32). Remarkably, CD8 + T-cell response was lower in the RA cohort compared to that observed in the HCWs.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, CD4 + T-cell frequency was higher compared to that observed for the CD8 + T cells. These data agree with the results from the HCWs cohorts (5,(27)(28)(29)(30)(31) and the COVID-19 convalescent subjects (17,32). Remarkably, CD8 + T-cell response was lower in the RA cohort compared to that observed in the HCWs.…”
Section: Discussionsupporting
confidence: 89%
“…It is known that mRNA vaccines induce a robust T cell response to emerging viral variants, and that the mix and match vaccine strategy offers robust immunogenicity and tolerable reactogenicity. The HCWs who were aware of such information showed a higher willingness to receive a third booster dose [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations with pseudoviruses possessing RBD mutations carried by variants of concern demonstrated that the neutralizing activity of plasma from vaccinated individuals showed a small but significant decreases of onefold to threefold against E484K, N501Y or the K417N + E484K + N501Y triple mutant 59 . Other data indicate that the effect of N501Y alone on neutralization is relatively modest, and other studies using sera from 20 participants in a trial of the BNT162b2 vaccine showed neutralizing titres equivalent to those of pseudoviruses carrying the N501 and Y501 mutations 82 . Other investigations with recombinant viruses carrying N501Y, ΔH69–V70 + N501Y + D614G or E484K + N501Y + D614G demonstrated that compared with the Wuhan-Hu-1 reference virus, only E484K + N501Y + D614G resulted in a small and modest reduction in neutralization by postvaccination sera elicited by two BNT162b2 doses, and only modest differences in neutralization were seen compared with the Wuhan-Hu-1 reference virus 83 .…”
Section: Vaccine Efficacy Against New Variantsmentioning
confidence: 99%